2018
DOI: 10.3892/etm.2018.6792
|View full text |Cite
|
Sign up to set email alerts
|

A study on the mechanism of agonists in regulating transcriptional level of pIgR in salivary gland epithelial cells

Abstract: The aim of the present study was to explore the mechanism of agonists in regulating transcriptional level of polymeric immunoglobulin receptor (pIgR) in salivary gland epithelial cells, thus revealing the defense effect of salivary immune on bacteria in the oral cavity. Sixty patients with oral bacterial infection and 70 patients suffering from oral diseases without bacterial infection were selected randomly from patients in Renmin Hospital of Wuhan University from April 2015 to April 2017. Ribonucleic acid (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…SGECs were isolated from salivary glands of mice according to a previous method [20]. Our study was in accordance with institutional guidelines from the Affiliated Hospital of Qingdao University.…”
Section: Isolation and Treatment Of Sgecsmentioning
confidence: 99%
“…SGECs were isolated from salivary glands of mice according to a previous method [20]. Our study was in accordance with institutional guidelines from the Affiliated Hospital of Qingdao University.…”
Section: Isolation and Treatment Of Sgecsmentioning
confidence: 99%
“…We confirmed the direct regulation of PIGR in HSG cells by Streptococcus mutans through in vitro experiments. A previous study reported similar results from in vivo experiments: salivary gland epithelial cells isolated from patients infected with oral Streptococci showed reduced Pigr expression (47). Streptococcus mutans is the major cause of dental caries (48); therefore, its inhibitory effect on Pigr is reasonable because it reduces the transportation of anti-caries IgA into the saliva.…”
Section: Discussionsupporting
confidence: 57%
“…Ovostatin homolog (OVOS) was subjected to IPR enrichment and was found to belong to the immunoglobulin E set. Interestingly, a non-secreted protein, the polymeric immunoglobulin receptor (PIGR), has been reported to be positively correlated with IgA concentrations in mouse saliva ( Huang et al., 2018 ; Gong et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%